Prenosologic evaluation of status in adult population living in area falled «Proton» launch vehicle - Musina, A.A.; Madenbay, K.M.; Smailova, A.A.; Beknazar, M.A. (KSU Publ., 2018)
It was evaluated functional status of women and men constantly living in area falled «Proton» launch vehicle. It was identified physiological features with considering living place in township. Studies have shown an accelerated rate of aging in both men and women, as well as differences in the degree of stress of the central heart rate control loop. Taking into account places of residence differences were found between the parameters of PP, PRV, MVB, ADP and IN indices, and in men in ADP, MVB, MBV and AP, indicating that differences are greater in speed and volume characteristics of the system blood circulation, and the most unsatisfactory ratio was registered in men of the Karsakpai settlement. In Karsakpai women, the pulse pressure index (PP) was maximum against the background of low values of minute blood deflection (MBV) with a high value of peripheral vascular resistance (PVR) and low mean dynamic pressure (ADP), which is considered a sign of stagnant phenomena in the vascular bed. Women of Zhezkazgan and men in the village Karsakpai and Satpayev have a fast aging pace and they should pay attention to the lifestyle and if necessary it is recommended to undergo additional examination.
«Протон» зымыран тасымалдағышы құлаған аймақта өмір сүретін ересек контингенттің нозологияға дейінгі мəртебесін бағалау
Донозологическая оценка статуса взрослого контингента, проживающего на территории падения ракетоносителя «Протон»
Keywords: adaptation; adult population; aging; cardiovascular system; environmental load; healthy lifestytle; heart rate variability; prenosologic diagnosis; rocket and space activities; prenosologic status